Fundamental Ideas of mathematics and the importance of affect-related aspects of learning - von der Bank, Marie-Christine (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Since the development of the concept of Fundamental Ideas, they point out that learning mathematics in schools must involve more than merely presenting these ideas. In addition, we must enable our students to develop a positive attitude towards learning, including affect-related aspects that inspire a sense of excitement about discovery and self-confidence in one’s abilities. In this paper a theory of Fundamental Ideas is presented, that combines and complements previous concepts. For implementing mathematical education in schools, this theory is reduced and solidified to its core. It can be used to analyse and create a learning setting focusing on affect-related aspects of learning and teaching mathematics. The usage is elucidated through an example, emphasising the planning of a lesson in the field of geometry.